2018
DOI: 10.1002/adem.201800457
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Model of Cellular Solids for Energy Absorption

Abstract: Cellular materials, also known as foams, have a variety of applications in the field of packaging, and shock mitigation in the case of crash of vehicles, due to their ability to protect goods by absorbing energy in the case of impact while reducing the transmitted loads. To properly design energy absorption devices and systems such as bumpers, road barriers, helmets, sole paddings, packages, etc. it is necessary to use precisely predictive models of cellular materials, in order to select the most suitable foam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In contrast, higher energy absorption and higher strength are characteristics of closed‐cell foams but at reduced efficiency due to the higher density. [ 3–9 ] Therefore, a foam with a hierarchical structure composed of regions of open‐cell and others of closed‐cell is optimal for improving the impact‐mitigation ability of structures to absorb the impact energy. [ 10,11 ] Nonetheless, regardless of the cell structure, the foam padding is required to lower the amplitude of the incoming force while broadening the peak of the force‐time history, hence allowing the body to respond with inducing injury naturally.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, higher energy absorption and higher strength are characteristics of closed‐cell foams but at reduced efficiency due to the higher density. [ 3–9 ] Therefore, a foam with a hierarchical structure composed of regions of open‐cell and others of closed‐cell is optimal for improving the impact‐mitigation ability of structures to absorb the impact energy. [ 10,11 ] Nonetheless, regardless of the cell structure, the foam padding is required to lower the amplitude of the incoming force while broadening the peak of the force‐time history, hence allowing the body to respond with inducing injury naturally.…”
Section: Introductionmentioning
confidence: 99%
“…where ε is the compressive strain, σ LEO is the compressive stress of the LEO model, and the oscillation fitting parameter ω is the only additional parameter compared to the Avalle model. [7] The fitting parameters are: σ p as the plateau stress, σ s as the linearhardening slope in the plateau region, σ d as the Rusch densification parameter, n as the Rusch densification exponent, and m as the linear-plateau transition parameter.…”
Section: Oscillation Modelsmentioning
confidence: 99%
“…where m, n, r, and s are fitting parameters. Avalle [7] updated the model to better capture plateau stresses apparent in the mechanical response as…”
Section: Oscillation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These concepts often consist of soft materials, such as hydrogels, and require external stimuli, such as magnetic field, mechanical stress, and temperature, to activate the tunable mechanical properties. Cellular structured materials are greatly used for energy absorbing applications [11][12][13][14]. Several research studies showed that graded cellular structures enabled gradual collapse leading to more energy absorption and this is beneficial for protecting payloads from dynamic loads [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%